Parity-nonconservation effect in the dielectronic recombination of polarized electrons with heavy He-like ions - Zaytsev, Vladimir; Maiorova, Anaa V.; Shabaev, Vladimir M.; Volotka, Andrey V.; Tashenov, Stanislav; Plunien, Günter; Stöhlker, Thomas (Physical review. A, Atomic, molecular, and optical physics, 2014)
We investigate the parity nonconservation (PNC) effect in the dielectronic recombination of a polarized electron with a heavy He-like ion into doubly excited [(1s2p1/2)0nκ]1/2 and [(1s2s)0nκ]1/2 states of a Li-like ion. We determine the nuclear charge number Z for which these opposite-parity levels are almost crossing and therefore the PNC effect will be significantly enhanced. Calculations are performed for quantum numbers n≥4 and κ=±1.